Integrating disciplinary-specific genre structure in discourse strategies to support disciplinary literacy - Rappa, N.; Tang, Kok-Sing (2018)
Classroom discourse plays an important role in shaping how students learn science in the classroom. Past research has examined how content area teachers use a variety of generic discourse strategies to foster classroom interaction and content mastery. However, few have focused on how teachers’ discourse strategy can be used in more specific ways to build subject-specialized genres of the discipline, such as scientific explanation. The purpose of this study is to examine how science teachers integrate disciplinary-specific genres in their discourse strategies to engage their students in thinking about the conceptual and epistemic aspects of the discipline. Through a three-year design research, four science teachers learned a genre-based instructional method designed to explicitly teach students how to construct scientific explanations. Lesson observations from these teachers before and after they learned the genre-based instruction were video-recorded and analyzed. It was found that with the incorporation of the genre-based instructional method, a discourse strategy that we call meta-discoursing was employed in ne w ways to facilitate the teaching of the explanation genre. Using multiple exemplars, we describe the ways in which this discourse strategy was enacted in tandem with the genre-based instructional method to facilitate disciplinary literacy through classroom talk.